The level of job satisfaction among a sample of social counselors in the elementary schools in the city of Lattakia - مرشد, ذوالفقار; هلا محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research aims to know the level of job satisfaction among a sample of social counselors in the elementary schools in the city of Lattakia. To achieve the goal of the research, a job satisfaction that related to social counselors questionnaire was created and it included six dimensions. The research sample consisted of (50) social counselors who were drawn using the intentional sampling method from the school of the city of Lattakia, the elementary schools, the researcher adopted the descriptive approach. The research reached a set of results indicating that job satisfaction came at an average level among social counselors. Lt was also found that there was no difference between the scores of the sample members on the job satisfaction questionnaire according to the gender variable. Also, no differences were detected among the sample members according to the variables of educational qualification and the number of the years of service.